Elucidating linkages between women's empowerment in livestock and nutrition: a qualitative study. Issue 4 (19th May 2018) - Price, Mindy; Galie, Alessandra; Marshall, Jennifer; Agu, Ngozichukwuka
ABSTRACT: This article investigates knowledge and perceptions of women's empowerment from the perspective of female livestock keepers and elucidates linkages between women's empowerment and household nutrition in relation to livestock. Eight focus groups with 62 female livestock keepers were conducted in Tanzania. Women's empowerment in livestock was associated with improved household nutrition. Other opportunities for empowerment were identified that could contribute to women's decision-making power. The article recommends that all development interventions in the livestock sector be gender sensitive and engage local men in conversations about gender inequities. It also discusses other pathways to increase women's empowerment and household nutrition.